2000
DOI: 10.1098/rspb.2000.1192
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression influences lifetime breeding success in a wild population of red deer (Cervus elaphus)

Abstract: Evolutionary and conservation biologists have a long-standing interest in the consequences of inbreeding. It is generally recognized that inbred individuals may experience reduced fitness or inbreeding depression. By the same token, relatively outbred individuals can have greater than average fitness, i.e. heterosis. However, nearly all of the empirical evidence for inbreeding depression comes from laboratory or domestic species. Inbreeding depression and heterosis are difficult to detect in natural population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
238
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(248 citation statements)
references
References 26 publications
8
238
0
2
Order By: Relevance
“…(a) Inbreeding depression in siring success and avoidance of inbreeding While the impact of inbreeding on male reproductive success was shown for some animal species [18,30,32], this study provides the first direct experimental evidence in plants that inbreeding directly and strongly decreased male fitness (siring success) under natural conditions. Previous studies reported inbreeding depression for in vitro pollen germination [26,28] and pollen performance in controlled pollinations [29], including S. latifolia [15].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…(a) Inbreeding depression in siring success and avoidance of inbreeding While the impact of inbreeding on male reproductive success was shown for some animal species [18,30,32], this study provides the first direct experimental evidence in plants that inbreeding directly and strongly decreased male fitness (siring success) under natural conditions. Previous studies reported inbreeding depression for in vitro pollen germination [26,28] and pollen performance in controlled pollinations [29], including S. latifolia [15].…”
Section: Discussionmentioning
confidence: 81%
“…A key question that has been understudied, owing to limited access to genetic markers in the past, is whether the high levels of inbreeding and relatedness that often characterize plant populations also impact pollen fate. Higher fitness of outbred individuals is a central prediction of evolutionary biology [32], and inbreeding and relatedness are expected to have major effects on the number, quality and genetic variability of offspring [4]. Here, we examined whether inbreeding, relatedness, plant phenotype and pollen dispersal jointly affected male fitness in an experimental population in which the level of inbreeding was experimentally controlled and spatial structure was randomized and accounted for statistically.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of inbreeding were first summarized by Darwin [6]. Since then, evidence of the negative impact of inbreeding on fitness and viability at both individual and population levels has accumulated [1,[7][8][9][10]. The expression of recessive deleterious mutations has been indicated as the main cause of inbreeding depression [11 -13].…”
Section: Introductionmentioning
confidence: 99%
“…Where compared, however, the majority of results point to males as the more fragile sex. For example, in wild populations a higher sensitivity to inbreeding for males has been suggested for red deer (Slate et al, 2000), although in an isolated population of song sparrows ID for lifetime reproductive success was greater for females (Keller, 1998). In the laboratory, male flour beetles experienced stronger ID than females did (Pray and Goodnight, 1995), and male virility in Drosophila, an important component of male fitness, appears to be more strongly affected by inbreeding than female fertility (Brittnacher, 1981).…”
Section: Introductionmentioning
confidence: 99%